Eksistensi Asuransi Bagi Masyarakat Indonesia - Faqihisyam Irfandy; Septiyan Dwi Anggara (Lembaga Pengembangan Kinerja Dosen, 2023)
You may have heard a lot about the function and role of insurance. As you know, insurance is a contract represented by a policy, in which an individual (the insured) can receive benefits for various risks that occur. The benefits of this coverage will protect individuals against various risks that result in financial losses. For the functions and roles of insurance itself, of course only according to the product. So, what is the role of insurance in the country's economy, society, the investment world, to individual businesses or businesses?